Human Resource Transformation at Al-Jam'iyatul Washliyah Educational Institution: Multi-site Research - Edi Sundowo; Rusydi Ananda; Zaini Dahlan (Journal La Edusci, 2026)
This multisite qualitative study explores the transformation of human resources at two Islamic educational institutions under Al-Jam’iyatul Washliyah: MAS Muallimin UNIVA Medan and MAS Al-Washliyah 12 Perbaungan. Using interviews, observation, documentation analysis, and institutional records, the research examines four core dimensions: the existing condition of human resources, the strategies employed to enhance teacher and staff capacity, the forms of transformation that strengthen performance and technological adaptation, and the institutional approaches used to navigate challenges and internal resistance. Findings show that both schools possess solid foundational structures adequate staffing in core subjects, strong collegial culture, and policies aligned with institutional values yet face persistent issues such as uneven workload distribution, limited welfare support, generational gaps in digital competence, and inconsistent data governance. Human resource transformation is driven through competency-based development, value-oriented recruitment, technology-assisted administration, and intergenerational mentoring, all supported by persuasive, participatory leadership rooted in Islamic ethics. The study concludes that sustainable transformation requires integrated strategies that merge professional capacity building, digital modernization, and reinforcement of religious identity. These findings contribute a novel hybrid model of HR development for Islamic educational institutions in contemporary contexts.